Audit Sistem Informasi Pada Website FKPQ Tanjungpinang Menggunakan Standar Cobit 5.0 Domain EDM (Evaluate, Direct, and Monitor) - Devi Asri Yana Vita; Vita Rahayu (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2025)
FKPQ is an abbreviation for Qur'an education community forum. FKPQ is assisted by using a website provided by the Ministry of Religion, namely the website emis.kemenag.go.id. This system provides a form for inputting various data starting from data related to the FKPQ itself to data from Koran education institutions (LPQ) which will be submitted to each LPQ. In using this system, LPQ experienced several problems related to system performance, therefore an information system audit was carried out using the COBIT 5.0 EDM domain standard which is useful for broadcasting the system and then providing controls or recommendations for improving system performance. The overall results obtained are that this emissions system is at capability level 2 in the managed process with a value of 2.5. This indicates that during the audit process, this EMIS system still needs a lot of improvements related to governance related to system performance, in this way it is related to the governance of election forms which must be prioritized with no forms that include the results of reporting LPQ data, so that This can reduce the processing time for filling in data on the emissions system. Apart from that, this improvement is also expected to reduce the burden on the LPQ because it does not need to carry out tasks that are not its responsibility.